Effect of cover-crop biomass, strip-tillage residue disturbance width, and PRE herbicide placement on cotton weed control, yield, and economics. (26th June 2021) - Price, Andrew J.; Nichols, Robert L.; Morton, Trent A.; Balkcom, Kipling S.; Grey, Timothy L.; Li, Steve
Abstract: Conservation tillage adoption continues to be threatened by glyphosate and acetolactate synthase–resistant Palmer amaranth and other troublesome weeds. Field experiments were conducted from autumn 2010 through crop harvest in 2013 at two locations in Alabama to evaluate the effect of integrated management practices on weed control and seed cotton yield in glyphosate-resistant cotton. The effects of a cereal rye cover crop using high- or low-biomass residue, followed by wide or narrow within-row strip tillage and three PRE herbicide regimens were evaluated. The three PRE regimens were (1) pendimethalin at 0.84 kg ae ha −1 plus fomesafen at 0.28 kg ai ha −1 applied broadcast, (2) pendimethalin plus fomesafen applied banded on the row, or (3) no PRE. Each PRE treatment was followed by (fb) glyphosate (1.12 kg ae ha −1 ) applied POST fb layby applications of diuron (1.12 kg ai ha −1 ) plus monosodium methanearsonate (2.24 kg ai ha −1 ). Low-residue plots ranged in biomass from 85 to 464 kg ha −1, and high-biomass residue plots ranged from 3, 119 to 6, 929 kg ha −1 . In most comparisons, surface disturbance width, residue amount, and soil-applied herbicide placement did not influence within-row weed control; however, broadcast PRE resulted in increased carpetweed, large crabgrass, Palmer amaranth, tall morning-glory, and yellow nutsedge weed control in row middles compared with plots receiving banded PRE. In addition, high-residue plots had increased carpetweed, common purslane, large crabgrass, Palmer amaranth, sicklepod, and tall morning-glory weed control between rows. Use of banded PRE herbicides resulted in equivalent yield and revenue in four of six comparisons compared with those with broadcast PRE herbicide application; however, this would likely result in many between-row weed escapes. Thus, conservation tillage cotton would benefit from broadcast soil-applied herbicide applications regardless of residue amount and tillage width when infested with Palmer amaranth and other troublesome weed species.